Simulation of heating and current drive sources for scenarios of the ITER research plan. (18th November 2021) - Schneider, Mireille; Lerche, Ernesto; Van Eester, Dirk; Hoenen, Olivier; Jonsson, Thomas; Mitterauer, V.; Pinches, S.D.; Polevoi, A.R.; Poli, Emanuele; Reich, Matthias
Abstract: Predicting the impact of heating and current drive (H&CD) sources is essential to evaluate the performance of ITER plasmas and to subsequently optimise the scenarios for the four stages of the ITER research plan. This should be done in the context of global transport calculations of complete plasma discharges. For this purpose, a dedicated workflow has been developed in the ITER integrated modelling and analysis suite as a modular component to be used together with transport solvers to quantify the dynamics of H&CD sources for the different phases of a plasma discharge, including possible synergetic effects between the heating sources. This paper presents the results of the combined modelling of H&CD sources for the ITER DT baseline 15 MA/5.3 T scenario including the synergy between neutral beam injection (NBI) of deuterium, fusion-born alpha particles and ion cyclotron resonance heating (ICRH) at the fundamental frequency of deuterium, showing modest synergetic effects. The results of the combined H&CD sources for an ITER 7.5 MA/2.65 T helium plasma of the second pre-fusion power operation phase (PFPO-2) are also shown, exhibiting more significant synergetic effects between the fundamental ICRH minority hydrogen heating and NBI hydrogen beams. Finally, a study of electron cyclotron heating absorption for an ITER helium PFPO scenario at 7.5 MA/2.65 T is also presented with a discussion on the edge parasitic absorption that arises under specific conditions.